(untitled) (Eurasian Scientific Herald, 2022)
This article discusses the specifics and advantages of distance learning in foreign language teaching. Another advantage of distance learning is that the student can study at a convenient time and even without leaving work. It is because of these advantages that this style is becoming more and more popular in the world